PENGARUH KOMPONEN ARUS KAS DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM (Studi Empiris pada Perusahaan Sektor Consumer Non-Cyclicals Yang Terdaftar di BEI Periode 2019-2023) - Indonesia Indonesia; Ajimat Ajimat (Prodi Akuntansi Syariah UIN Sulthan Thaha Saifuddin Jambi, 2025)
This study aims to examine the Influence of Cash Flow Components and Company Size on Stock Returns in Consumer Non-Cyclical sector companies in 2019-2023. The sampling method used in this study is Purposive sampling. The type of research in this study is quantitative, obtained 29 companies that were used as research samples with observations for 5 (five) years, so that the total observation was 145 companies that issued financial reports consistently and provided variable data information needed by researchers in 2019-2023. This study was conducted with the help of Eviews 13. The results of this study indicate that Operational Cash Flow has no effect on Stock Returns. Investment Cash Flow has no effect on Stock Returns. Funding Cash Flow has no effect on Stock Returns. Company Size has a significant effect on Stock Returns. Operational Cash Flow, Investment Cash Flow, Funding Cash Flow, and Company Size, simultaneously have a joint effect on Stock Returns.